2014
DOI: 10.1111/imb.12152
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs of two medically important mosquito species: Aedes aegypti and Anopheles stephensi

Abstract: MicroRNAs (miRNAs) are endogenous, single-stranded small RNAs that have important regulatory functions at the post-transcriptional level. Here, we characterize miRNAs in two divergent mosquito species, Aedes aegypti and Anopheles stephensi, through deep sequencing of small RNAs spanning all developmental stages. We discovered eight novel miRNAs in Ae. aegypti and 20 novel miRNAs in An. stephensi, which enabled the first systematic analysis of miRNA evolution in mosquitos. We traced the phylogenetic history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 65 publications
0
54
0
Order By: Relevance
“…9,10,[28][29][30][31][32] Phenotypic divergence among animal species may be due in part to lineage-and species-specific regulation of gene expression by miRNAs. miRNAs restricted to mosquitoes may contribute to mosquito-specific functions and, as such, have potential for contributing to the development of novel mosquito control approaches.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,[28][29][30][31][32] Phenotypic divergence among animal species may be due in part to lineage-and species-specific regulation of gene expression by miRNAs. miRNAs restricted to mosquitoes may contribute to mosquito-specific functions and, as such, have potential for contributing to the development of novel mosquito control approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by us and others have shown that members of one of these clusters (mir-309 6) in Drosophila are strongly up-regulated in the early fly blastoderm (Biemar et al 2005;Ninova et al 2014), and that members of the homologous clusters in A. mellifera (mir-3478 318) and mosquitoes (mir-309 286) are also highly expressed in early embryos (Zondag et al 2012;Hu et al 2014). In addition, the mosquito-specific mir-2941 2946 cluster, whose 3 ′ mature sequences have the same seed as miR-3889-3p in T. castaneum, are the most abundant microRNAs in the early stages of development (Hu et al 2014). We detect nascent primary transcripts of mir-9d 3791 and mir-3889 3843 in the early blastoderm nuclei of T. castaneum by in situ hybridization (Supplemental Fig.…”
Section: Developmental Expression Of Conserved and Nonconserved Micromentioning
confidence: 93%
“…5C); clusters encoding homologs of the conserved mir-9, mir-2944, mir-279, mir-3791, and mir-309 families are found in other insect lineages and represent one of the most extreme examples of microRNA gain, loss, duplication, and rearrangement reported to date (Ninova et al 2014). Previous studies by us and others have shown that members of one of these clusters (mir-309 6) in Drosophila are strongly up-regulated in the early fly blastoderm (Biemar et al 2005;Ninova et al 2014), and that members of the homologous clusters in A. mellifera (mir-3478 318) and mosquitoes (mir-309 286) are also highly expressed in early embryos (Zondag et al 2012;Hu et al 2014). In addition, the mosquito-specific mir-2941 2946 cluster, whose 3 ′ mature sequences have the same seed as miR-3889-3p in T. castaneum, are the most abundant microRNAs in the early stages of development (Hu et al 2014).…”
Section: Developmental Expression Of Conserved and Nonconserved Micromentioning
confidence: 97%
“…In insects, the changes to the cluster were complex, with more new additions, although Mir-9 and Mir-2944 remained in the cluster and duplicated in higher insects. This cluster has been found to be highly expressed in early embryos of flies, bees, mosquitoes and beetles (Zondag et al, 2012;Hu et al, 2014;Ninova et al, 2014;Ninova et al, 2016). Its highly varied composition and functional evolution deserve special attention and in-depth research.…”
Section: The Evolutionary Perspective Of Conserved Mirna Clustersmentioning
confidence: 99%